The Moral Intensity of Privacy: An Empirical Study of Webmaster' Attitudes - Shaw, Thomas R. (2003)
Webmasters are a key moral agent in the issue of privacy. This study attempts to understand the factors underlying their attitudes about privacy based on the theory of moral intensity. Webmasters of high-traffic sites were invited via email to participate in a web-based survey. The results support the application of moral intensity to the domain of privacy and the population of webmasters – both outcomes and social norms have statistically significant main effects on attitudes. The results also suggest a reconfiguration of the dimensions of moral intensity. This is based on the observation that proximity to the organization has a negative main effect on attitudes, and it moderates the relationship between social norms and attitudes. The original theory of moral intensity did not acknowledge the possibility of this moderating role for proximity. These observations have important implications for future research and practice in the areas of privacy, moral intensity, and ethical decision making.
Keywords: webmasters; Privacy; Moral Intensity; information ethics; Ethical decision making; computer ethics